Institutional principles of digitalization of the construction industry - Shkuratov, O.; Chudovska, V. (Ways to Improve Construction Efficiency, 2023)
It has been proven that the use of digital technologies in the construction industry allows to automate and optimize the processes of design, planning and management of construction production. This leads to a reduction in the time and costs of work, as well as an increase in the quality and safety of construction objects. An analysis of the global and domestic practice of using digital technologies in the construction industry was carried out. The conditions under which the digitization process is organized and the factors that limit the development of the digital potential of the construction industry are determined. The available potential for the development of information technologies and the introduction of their products and services, as well as the readiness of construction enterprises for digitalization of business, was determined. At the same time, a number of factors are identified that limit the development of the digital potential of the construction complex and are formed as a result of the minimization of organizational and institutional initiatives of the authorities, the low level of development of the digital economy sector in the country, and the imperfection of the current regulatory and legal support. It was found that the regulation of the use of BIM technologies in design and construction tasks is evidence of a two-way motivation for the transition to BIM, both from the point of view of business institutions and from the state side, especially at the regional level during the development of the digital potential of the country’s construction complex. The exclusivity and objective influence of the institutional environment of digitalization of construction on the formation of the digital economy, which is based on the development of digital infrastructure and requires the formation of modern institutional support, has been proven. The system of forming the institutional environment of digitalization of construction is substantiated, covering economic, ecological, social, cultural, regulatory and political tools for the development of digital technologies in the construction industry, forming a system of social-production, financial-economic and regulatory relationships. During the study of the institutional environment that was formed in the construction industry of the country during the transformation processes in the digital economy and other spheres of human activity, the influence of formal and informal institutions on the effectiveness of the functioning of construction entities is revealed. It is argued that the institutional environment for the development of the digital economy in the construction industry is the basis that forms and influences the symbiosis of economic entities, consumers, and the state with the innovative environment and directs the vector of institutional transformations in the field of information technologies..